2005
DOI: 10.1002/jmor.10367
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal morphology of the forefoot in shrews (Mammalia: Soricidae) of the genus Cryptotis, as revealed by digital X‐rays

Abstract: Variation in the forefoot skeleton of smalleared shrews (family Soricidae, genus Cryptotis) has been previously documented, but the paucity of available skeletons for most taxa makes assessment of the degrees of intraspecific and interspecific variation difficult. We used a digital X-ray system to extract images of the forefoot skeleton from 101 dried skins of eight taxa (seven species, including two subspecies of one species) of these shrews. Lengths and widths of each of the four bones of digit III were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 16 publications
2
40
0
Order By: Relevance
“…Study of forefoot skeletal morphology among some soricine shrews has helped to identify a broader array of ecological diversity in the subfamily than had been appreciated (Woodman and Timm 1999;Woodman 2010Woodman , 2011aWoodman and Gaffney 2014), and variation in the bones of the forefoot is of sufficient magnitude to distinguish species and even subspecies (Woodman and Morgan 2005;Woodman and Stephens 2010;Woodman 2011b). As for other vertebrates, complete prepared skeletons of shrews and many other small mammals are relatively scarce in systematic collections (Bell and Mead 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Study of forefoot skeletal morphology among some soricine shrews has helped to identify a broader array of ecological diversity in the subfamily than had been appreciated (Woodman and Timm 1999;Woodman 2010Woodman , 2011aWoodman and Gaffney 2014), and variation in the bones of the forefoot is of sufficient magnitude to distinguish species and even subspecies (Woodman and Morgan 2005;Woodman and Stephens 2010;Woodman 2011b). As for other vertebrates, complete prepared skeletons of shrews and many other small mammals are relatively scarce in systematic collections (Bell and Mead 2014).…”
mentioning
confidence: 99%
“…As for other vertebrates, complete prepared skeletons of shrews and many other small mammals are relatively scarce in systematic collections (Bell and Mead 2014). The skeleton of the forefoot is typically preserved in traditional dried skin preparations, however, and it can be imaged using digital x-ray technology (Woodman and Morgan 2005;Woodman and Stephens 2010;Sargis et al 2013aSargis et al , 2013b. To study variation within and among species of myosoricines, we x-rayed the forefeet of 9 species of these shrews encompassing all 3 recognized genera.…”
mentioning
confidence: 99%
“…It was noted that the forefeet of species within the parva-group did not exhibit any of these forelimb or forefoot modifications. Research into the nature of the structural modifications of the forefeet by use of a digital X-ray system illustrated how the enlargement of the forefeet occurred relative to each of the bones in the manus (Woodman and Morgan 2005). Research reported by these investigators supported the speciesgroups first proposed by Choate (1970).…”
Section: Cryptotismentioning
confidence: 84%
“…Some studies suggest that the external morphology of the legs among the different groups of species in the genus Cryptotis (particularly the development of the front legs with claws and humerus), provides information on their evolutionary history and food preferences (e. g., Woodman et al 2003;Woodman and Morgan 2005). In the case of C. aroensis, Quiroga-Carmona and Molinari (2012) propose an apparent association with a more specialized diet including underground prey, due to the ease of digging provided by its developed front legs.…”
Section: Discussionmentioning
confidence: 99%